Lipoxin A4 Inhibits NLRP3 Inflammasome Activation in Rats With Non-compressive Disc Herniation Through the JNK1/Beclin-1/PI3KC3 Pathway - Jin, Jin; Xie, Yonggang; Shi, Cunxian; Ma, Jiahai; Wang, Yihao; Qiao, Leyan; Li, Kezhong; Sun, Tao (Frontiers in Neuroscience, 2020)
Background Non-compressive disc herniation is induced by an inflammatory response from the nucleus pulposus tissue and nerve roots. Lipoxins (LXs) are important endogenous anti-inflammatory mediators in the body, helping to inhibit neutrophil recruitment and stimulate autophagy in monocytes and macrophages. Here, we investigated the molecular mechanisms underlying the effects of exogenous lipoxin administration on rats with non-compressive disc herniation. Method A non-compressive disc herniation model was established in rats. Fifty rats were randomly divided into: sham group, model group, PI3K inhibitor (LY294002) group, lipoxin A4 group (LXA4), and PI3K inhibitor and lipoxin A4 group (LY294002 + LXA4). Similar groupings were established for rat spinal neurons. Changes in the mechanical pain threshold and thermal pain threshold were monitored at different times. The expression of proinflammatory and anti-inflammatory mediators was assessed by ELISA, while immunohistochemistry was employed to measure the expression levels of NLRP3 and p-JNK1. The expression levels of autophagy-related proteins were measured by western blot. Results In vivo, the pain threshold was markedly decreased in the model group at each time point examined compared with that in sham group. LY294002 treatment further reduced the pain threshold. After LXA4 injection, the pain threshold was significantly increased, and the effect of LY294002 was significantly weakened (p < 0.05). The levels of proinflammatory cytokines were increased in rats with non-compressive disc herniation, and these levels were further increased by LY294002 treatment (p < 0.05). However, treatment with LXA4 significantly reduced the levels of these proinflammatory cytokines in the model group (p < 0.05). The opposite effect was observed for anti-inflammatory mediators. The expression of NLRP3 was largely increased in the model group compared with that in the sham group (p < 0.05). Treatment with LY294002 also increased the NLRP3 expression level, while the administration of LXA4 elicited the opposite effect. Furthermore, western blot analysis showed that the expression of autophagy-related proteins was greatly decreased in the model group, whereas it was significantly increased in the LXA4 group (p < 0.05). The in vitro results were consistent with the outcomes observed in vivo. Conclusions These data suggested that LXA4 inhibited NLRP3 activation in rats with non-compressive disc herniation by regulating the JNK1/beclin-1/PI3KC3 pathway.